Thrombin Induces Increased Expression and Secretion of VEGF from Human FS4 Fibroblasts, DU145 Prostate Cells and CHRF Megakaryocytes - Huang, Y-Q.; Li, J-J.; Hu, L.; Lee, M.; Karpatkin, S. (Thrombosis and Haemostasis, 2001)
Angiogenesis is required for tumor growth and metastasis. It has recently been suggested that thrombin is a potent promoter of angio-genesis. We therefore examined the possibility that thrombin could be inducing the expression of vascular endothelial growth factor (VEGF), which promotes endothelial growth. Primary human FS4 fibroblasts as well as tumor cell lines: prostate DU145 and megakaryocyte CHRF were incubated with thrombin (0.25-1 unit/ml) for 1-8 hrs and then examined for mRNA by Northern Analysis. Enhanced mRNA (~3-4 fold over base line) was noted at 2-4 hrs, with 0.5 u/ml thrombin. The effect was specific for thrombin activity on its PAR-1 receptor, since equal units of hirudin completely inhibited the response and the thrombin effect could be mimicked with the 14 mer thrombin receptor activation peptide (TRAP). Upregulation of mRNA was associated with enhanced VEGF protein synthesis and secretion as assayed by immunoblot. Enhanced expression of VEGF mRNA was not secondary to enhanced transcription (nuclear run on experiments), but due to an >3 fold stabilization of mRNA (Actinomycin D chase experiment). Enhanced VEGF mRNA stabilization is promoted by the PI3Kinase and serine/threonine kinase pathways, since thrombin-induced mRNA expression is inhibited by Wortmanin and H7. No effect was noted with the MAPKinase inhibitor, PD98059. Thus, thrombin-induced tumori-genesis and metastasis is associated with enhanced VEGF protein synthesis and secretion via the stabilization of VEGF mRNA promoted by the PI3Kinase and serine/threonine kinase pathways. This could help explain how thrombin promotes angiogenesis.
Keywords: Thrombin; VEGF; angiogenesis; PI3Kinase; serine/threonine kinase